The influence of anisotropic nano- to micro-topography on in vitro and in vivo osteogenesis. (March 2015) - Azeem, Ayesha; English, Andrew; Kumar, Pramod; Satyam, Abhigyan; Biggs, Manus; Jones, Eleanor; Tripathi, Bhawana; Basu, Nandita; Henkel, Jan; Vaquette, Cédryck; Rooney, Niall; Riley, Graham; et al.
Aim: Topographically modified substrates are increasingly used in tissue engineering to enhance biomimicry. The overarching hypothesis is that topographical cues will control cellular response at the cell–substrate interface.Materials & methods: The influence of anisotropically ordered poly(lactic-co-glycolic acid) substrates (constant groove width of ˜1860 nm; constant line width of ˜2220 nm; variable groove depth of ˜35, 306 and 2046 nm) on in vitro and in vivo osteogenesis were assessed.Results & discussion: We demonstrate that substrates with groove depths of approximately 306 and 2046 nm promote osteoblast alignment parallel to underlined topography in vitro . However, none of the topographies assessed promoted directional osteogenesis in vivo .Conclusion: 2D imprinting technologies are useful tools for in vitro cell phenotype maintenance.